Unraveling the stress response and biosorption mechanisms of Aspergillus niger to rare earth element cerium(III) based on transcriptomics and DNA methylomics - Liu, Jingqi; Tan, Donghua; Qiu, Huangfeng; Liang, Yuting; Wu, Haiyan; Yang, Yu; Zhao, Hongbo (Frontiers in Microbiology, 2025)
Rare earth elements (REEs) represent critical industrial resources, yet conventional extraction methods face substantial environmental and efficiency constraints. Fungal bioleaching emerges as an eco-friendly alternative, leveraging organic acid secretion to facilitate REEs dissolution and adsorption. However, progressive REEs accumulation inhibits microbial activity, with fungal resistance mechanisms remaining incompletely understood. Here, we report the discovery of Aspergillus niger FH1, a highly REEs-tolerant strain exhibiting remarkable Ce(III) tolerance (600 mg/L maximum) and achieving 74.05% adsorption efficiency under optimized conditions. Integrated physicochemical characterization (SEM, FTIR, XPS) revealed dual adsorption mechanisms: physical entrapment evidenced by Ce(III)-induced cellular invagination, and chemical monolayer binding via extracellular functional group coordination (amino, hydroxyl, carboxyl, carbonyl, phosphate), with specific moieties enabling Ce(III) capture through surface complexation. Transcriptomic analysis identified 3,733 differentially expressed genes under Ce(III) stress. Functional annotation (GO/KEGG) demonstrated: (1) Significant repression of oxidative phosphorylation genes; (2) Concomitant upregulation of glycolysis, pentose phosphate pathway, and amino acid metabolism genes indicating metabolic rerouting for energy maintenance; (3) Enhanced expression of antioxidative/chelating metabolite synthesis pathways. Whole-genome bisulfite sequencing revealed conserved global 5mC DNA methylation levels (0.32% vs. 0.36% in controls) with preferential CHH-context targeting. Collectively, these adaptation strategy combines extracellular sequestration, metabolic plasticity, and stress mitigation to confers exceptional resilience against rare earth metal toxicity. The demonstrated adsorption-tolerance synergy positions A. niger FH1 as an important bioagent for sustainable recovery of recalcitrant rare earth resources.